Forecasting accuracy evaluation of tourist arrivals. (March 2017) - Hassani, Hossein; Silva, Emmanuel Sirimal; Antonakakis, Nikolaos; Filis, George; Gupta, Rangan
Highlights: This study forecasts European tourism demand using nine forecasting models. Successfully introduces SSA-R and TBATS models for tourism demand forecasting. No single model can provide the best forecast across all horizons. SSA, ARIMA and TBATS are viable options for forecasting European tourist arrivals. SSA-R is on average best across all horizons. Abstract: This paper evaluates the use of several parametric and nonparametric forecasting techniques for predicting tourism demand in selected European countries. We find that no single model can provide the best forecasts for any of the countries in the short-, medium- and long-run. The results, which are tested for statistical significance, enable forecasters to choose the most suitable model (from those evaluated here) based on the country and horizon for forecasting tourism demand. Should a single model be of interest, then, across all selected countries and horizons the Recurrent Singular Spectrum Analysis model is found to be the most efficient based on lowest overall forecasting error. Neural Networks and ARFIMA are found to be the worst performing models.